Soil Morphology Studies on Slash and Burn Forest System in Koto XI Tarusan District Pesisir Selatan Region - TANCO, RYAN; Juita, S.Pd. M.Si, Erna; Thesiwati, SP., M.Si, Aslan Sari (Pendidikan Geografi, 2014)
ABSTRACTÂ Â This research is motivated a system of slash and burn forest clearing is done in the community in Koto XI Tarusan district. This study aims to: 1) Condition of soil physical (texture, structure, consistency and permeability soil) on forest slash and burn system in Koto XI Tarusan District Pesisir Selatan Region, 2) the chemical properties of soil conditions (soil reaction (pH) on the slash in Koto XI Tarusan District Pesisir Selatan Region and 3) biological properties of soil conditions (soil organic matter) in the slash and burn system of forest in Koto XI Tarusan District Pesisir Selatan Region.The sampling technique was purposive sampling, the sample was appointed by the intended use of the land which represent areas of research. Data analysis used descriptive analysis go round the tables in the form of a comparison between the characteristics of the soil properties (soil texture, soil structure, soil consistency, soil pH, and organic matter) than the level of suitability of land for rice crops.The results showed that: (1) The physical properties of the soil in the entire study sample obtained clay texture with smooth category, good soil structure on the category 2 and category rather well sampled at 2 samples, the consistency of the soil in the bad category 2 samples and 2 samples of both categories and slow soil permeability criteria and criteria on 2 samples were in 2 samples. (2) The chemical properties of the soil (soil pH) category rather poorly contained in either category 3 samples and samples at 1, (3) biological properties of soil (Organic Material) category was the 2 samples and the high category in 2 samples, and ( 4 ) morphological land on slash and burn system in Koto XI Tarusan District both categories in 2 samples and morphology were in 2 samples